2012
DOI: 10.1007/s10014-012-0128-7
|View full text |Cite
|
Sign up to set email alerts
|

Extraventricular neurocytoma of the sellar region with spinal dissemination

Abstract: Extraventricular neurocytoma (EVN) is a rare tumor that mainly occurs in the cerebral hemispheres and spinal cord. Sellar neurocytoma is extremely rare, with only two previously reported cases. We report a sellar EVN in a 48-year-old man presenting with visual impairment. This tumor was partially resected. The residual tumor disappeared on MRI with adjuvant radiotherapy. However, 2 years later the tumor recurred with craniospinal dissemination, which is also very rare, with only four previously reported cases.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Sellar and suprasellar extraventricular CN are extremely rare, and only 12 reported cases[451011121416171819] were identified during our review of the PubMed and Bireme databases using the following keywords: neurocytoma, central, extraventricular, sellar, suprasellar, pituitary, and hypophysis. The clinical, radiological, pathological, and treatment features of these cases are shown in Table 1.…”
Section: Discussionmentioning
confidence: 99%
“…Sellar and suprasellar extraventricular CN are extremely rare, and only 12 reported cases[451011121416171819] were identified during our review of the PubMed and Bireme databases using the following keywords: neurocytoma, central, extraventricular, sellar, suprasellar, pituitary, and hypophysis. The clinical, radiological, pathological, and treatment features of these cases are shown in Table 1.…”
Section: Discussionmentioning
confidence: 99%
“… Transsphenoidal Radiotherapy after operation partial tumor resection Vision improved and headache relieved. No recurrence was found in 1 year Wang et al ( 2012 ) Female/50 years Pituitary adenoma or Craniopharyngioma Decreased vision,, bitemporal hemianopia MRI: A mass insellar region, extended to sphenoid and cavernous sinus CT: Spot calcification Transsphenoidal Radiotherapy after operation Partial tumor resection Vision improved, no recurrence was found in 1 year Yang et al ( 2009 ) Female/46 years Meningioma Decreased vision of bilateral eyes MRI: A round mixed signal intensity insellar region, with slight enhancement Transpterional, radiotherapy after operation Partial tumor resection Right vision improved, but tumor recurred in 6 months Kawaji ( 2014 ) Male/48 years Pituitary adenoma Decreased vision CT: An suprasellar isodense mass MRI: A round suprasellar mix-signal intensity, with obvious enhancement Bi-subfrontal Radiotherapy after operation Partial tumor resection Vision improved, and residual tumor disappeared after radiotherapy, but brain and spinal cord metastasis was found in 6 years later Wang et al ( 2013 ) Female/23 years Pituitary adenoma Decreased vision, headache CT: A hyper-density mass in sellar region MRI: intense homogeneous enhancement Transsphenoidal, radiotherapy after operation Partial tumor resection Vision improved and headache relieved Present case Male/25 years Pituitary adenoma or meningioma Decreased vision in left eye MRI: A roundish mass in the sellar and suprasellar region …”
Section: Discussionmentioning
confidence: 99%
“…The EVNs were more likely to recur in patients at the age of below 18 years old or above 50 years old (Patil et al 2014 ). In nearly 100 patients with EVNs reported by Kawaji et al ( 2014 ), five had metastatic focus with one located at cerebellum, three in craniospinal region and one in distant dural. Longer follow-up is needed, especially among patients with residual tumors after operation or atypical tumors (Ki67 > 2 %) and patients at age below 18 years old/above 50 years old.…”
Section: Discussionmentioning
confidence: 99%
“…Stapleton et al recently reported a rare case in the pediatric population of a diffuse CN with craniospinal dissemination that was identified at the time of the initial diagnosis by the immunohistochemical results of an elevated Ki-67 proliferation index (53). To date, there have been five reported cases of EVN with craniospinal dissemination (8,30,49,5456), including four males (7, 24, 48 and 75 years old) and one female (71 years old). Two of the patients showed drop dural metastasis and one tumor was initially located in the sellar region and was associated with multiple remote disseminations in the spinal cord and drop metastasis in the frontal cranial base in the route of the initial surgery (54).…”
Section: Discussionmentioning
confidence: 99%
“…To date, there have been five reported cases of EVN with craniospinal dissemination (8,30,49,5456), including four males (7, 24, 48 and 75 years old) and one female (71 years old). Two of the patients showed drop dural metastasis and one tumor was initially located in the sellar region and was associated with multiple remote disseminations in the spinal cord and drop metastasis in the frontal cranial base in the route of the initial surgery (54). The other tumor was initially located in the left occipital-parietal lobe and was associated with drop metastasis along the frontotemporal dura with an intratumoral hemorrhage outside the field of the initial surgery (56).…”
Section: Discussionmentioning
confidence: 99%